2006
DOI: 10.2174/138161206777442119
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic AIDS Vaccines

Abstract: Therapeutic HIV vaccines represent promising strategy as an adjunct or alternative to current antiretroviral treatment options for HIV. Unlike prophylactic AIDS vaccines designed to prevent HIV infection, therapeutic vaccines are given to already infected individuals to help fight the disease by modulating their immune response. The first immunotherapeutic trial in AIDS patients was conducted in 1983. Since then several dozen conventional therapeutic vaccine trials have been carried out. Unfortunately, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 156 publications
(190 reference statements)
0
11
0
Order By: Relevance
“…Microbicides circumvent many of the immunological difficulties associated with HIV vaccine development and make topical formulations a more realistic goal, especially in the short term (27,28). The most promising strategy currently being pursued is the utilization of intravaginal delivery systems for microbicides (13,26,(29)(30)(31)(32)(33)(34).…”
Section: Methodsmentioning
confidence: 99%
“…Microbicides circumvent many of the immunological difficulties associated with HIV vaccine development and make topical formulations a more realistic goal, especially in the short term (27,28). The most promising strategy currently being pursued is the utilization of intravaginal delivery systems for microbicides (13,26,(29)(30)(31)(32)(33)(34).…”
Section: Methodsmentioning
confidence: 99%
“…Since the first immunotherapeutic clinical trial for HIV/AIDS in 1983, various trials have been carried out and are still ongoing [9093]. Unfortunately, despite the preclinical studies that showed enhanced immune responses, most of the clinical studies have consistently failed to provide clinical improvements for patients [90].…”
Section: Immunotherapy For Hiv/aidsmentioning
confidence: 99%
“…Others were derived from the blood of HIV-infected patients. The clinical trials were recently reviewed [12]. Many of the trials were uncontrolled and enrolled relatively few patients.…”
Section: Outcome Measuresmentioning
confidence: 99%